PENGARUH PENGGUNAAN MEDIA INSTAGRAM BERMUATAN PROBLEM POSING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA - Dea Yustina; Iwit Prihatin; Hodiyanto Hodiyanto (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study was to determine: (1) students' mathematical communication skills before being given learning using Instagram media containing problem posing in the system of linear equations and inequalities; (2) students' mathematical communication skills after being given learning using Instagram media containing problem posing in the material of linear equations and inequality systems; (3) the effect of using Instagram media containing problem posing on students' mathematical communication skills in the material of linear equations and inequality systems in class X SMA Koperasi Pontianak; (4) the magnitude of the influence by using Instagram media with problem posing content on students' mathematical communication skills in the material of linear equations and inequality systems in class X SMA Koperasi Pontianak. This reseach method is to use the Pre Eksperimental Desaign method. Sampling was done by saturated sampling technique. The instrument for collecting data was a test of mathematical communication skills. The data analysis in this study used descriptive data analysis and inferential statistic. The results of the study were that before the learning model was applied with an average student score of 39.97 which was classified as a failure, and after being applied the learning model with an average of 58.07 was sufficient so that there was an increase, from the research results there was also an influence and also the magnitude of the effect. After learning is applied using instructional media that contains problem posing on students' mathematical communication skills.